The role of Phytophthora infestans oospores in primary infection of potato foliage in Poland. - Zarzycka, Hanna; Lebecka, Renata; Sobkowiak, Sylwester (Plant Breeding and Seed Science, 2001)
The study on oospore formation ability under natural conditions was carried out on the base of comparative characterization of four local populations of P. infestans. It was found that oospores can be formed in potato tissues under natural conditions. The comparison of proportion of both mating types isolates, high level of race complexity and racial diversity indicates, that oospores in experimental fields could play a role as a source of primary inoculum in three experimental localities in Boguchwała, in Przychojec and in Olesno Śląskie.The oospores were produced also in all combinations of pot and field experiments. They were formed most abundantly, when the potato plants were inoculated with mixed inoculum consisted of A1 and A2 spores, in 1:1 ratio and significantly less abundantly, when the inoculum was dominated by one of mating type isolate. The effect of time of subsequent inoculation with A1 or A2 isolates on oospore formation was observed: significantly more oospores were formed when the plants were inoculated with both mating types at the same time.